Psychometric properties and validation of a four-item version of the Strauss-Carpenter scale in bipolar disorder - Alberich, Susana; Barbeito, Sara; González-Ortega, Itxaso; Ugarte, Amaia; Vega, Patricia; Ruiz de Azúa, Sonia; López, Purificación; Zorrilla, Inaki; González-Pinto, Ana (International Journal of Bipolar Disorders, 2018)
Background: Bipolar disorder is a chronic illness that impairs functioning and affects the quality of life of patients. The onset of this illness usually occurs at an early age, and the risk of relapse remains high for decades. Thus, due to the great clinical relevance of identifying long-term predictors of functioning in bipolar disorder, Strauss and Carpenter developed a scale composed of items known to have prognostic value. Methods: To determine the clinical usefulness of the four-item Strauss-Carpenter scale in bipolar disorder, a 1-year prospective follow-up study was carried out. The internal consistency, convergent and discriminant validity, and test-retest reliability of the scale were assessed. We also compared the Strauss-Carpenter scale with the reference scales Global Assessment Functioning (GAF), Clinical Global Impression for Bipolar Disorder, the Modified Version (CGI-BIP-M) and the Sheehan Disability Scale (Sheehan). Additionally, a cut-off point for remission was established. Results: The total sample was composed of 98 patients with a diagnosis of bipolar disorder. The four-item version of the Strauss-Carpenter scale showed to have appropriate psychometric properties, comparable to those of reference scales. The best cut-off point for remission was 14. Conclusions: The four-item version of the Strauss-Carpenter scale has suitable validity and reliability for the assessment of functioning in patients with bipolar disorder.
Keywords: strauss–carpenter; functioning; bipolar; prognosis; outcome; Emerging; Scopus